Peningkatan Kemampuan Mengajar Berbasis Keterampilan Abad 21 Melalui Supervisi Akademik Metode Pemodelan Teman Sejawat Bagi Guru SD Gugus I Kecamatan Rappocini Kota Makassar - tamrin, tamrin (Universitas Negeri Makassar, 2021)
The main objective of this research is to improve the skills-based teaching skills of the 21st century through academic supervision of peer modeling methods for teachers of SD Gugus I, Rappocini District, Makassar City. In accordance with the objectives, in this school action research, 24 research subjects were selected who were intervened in the academic supervision of peer modeling methods in the form of action research. Based on the results of the data analysis above, it can be understood that both the ability to design lesson plans and the ability to carry out 21st-century skills-based learning activities from pre, cycle I, to cycle II have increased, namely the average score in making pre-cycle lesson plans is 2.171, cycle I increase to 3.02, and the second cycle 3,734. Whereas the ability to implement 21st-century skills-based learning the average score in the pre-cycle was 2.84, the first cycle increased to 3.30, and the second cycle was 3.53. If you look at the predetermined criteria, the average ability to design RPP is categorized as good. Likewise, the ability to carry out 21st-century skills-based learning is also categorized as good. Based on these data, it can be concluded that the teaching ability of 21st-century skills-based teachers in Cluster I, Rappocini District, Makassar City, especially for 24 people, has increased after the application of peer modeling-based academic supervision.